Systematic Review of Malaysia Technical and Vocational Education (TVET) sustainability framework to increase the marketability of graduates using PRISMA - Ridzwan Che Rus,; Mohd Azlan Mohammad Hussain,; Mohd Firdaus Mustaffa Kamal,; Zaliza Hanapi,; Idris, Mariam Oluwatoyin; Bamiro, Nurudeen Babatunde; Kayode, Bakare Kazeem (Penerbit Universiti Kebangsaan Malaysia, 2023)
The marketability of Technical and vocational education and training (TVET) graduates is a key factor in promoting Malaysia’s economic growth and development. Therefore, seeking a sustainable marketability framework for TVET will reduce educational wastage in TVET, increase enrolment, increase TVET sectoral contributions to GDP, and provide justification for taxpayer money used to finance the institution. Only a few studies have attempted to review the literature on this topic systematically. The Springer, Taylor & Francis, Scopus, and Google Scholar databases are employed in this systematic literature review, which is guided by the PRISMA (preferred reporting items for systematic reviews and meta-analysis) standards. A rigorous keyword search of the online databases produced 71 papers from 2017 to 2022, 29 of which were research that was relevant to the issue. The findings revealed that curriculum-related factors, skill gap factors, and poor stakeholder engagement are the basic factors impacting the marketability of the TVET graduate. The study recommends that The TVET regulatory bodies should strive to embark on curriculum revision to close the skill gap between the classroom and the industry, The curriculum of TVET should be improved and updated in every five years to catch up with industrial needs and there should be an effective partnership in all ramifications between TVET institutions and the industry.